IMPLEMENTATION OF A WAREHOUSE MANAGEMENT SYSTEM (WMS) TO IMPROVE OPERATIONAL EFFICIENCY - Sri Gusti Rezeki; Rahmi Syahriza; Nurbaiti Nurbaiti (JURNAL PROFIT, 2025)
This study aims to analyze the implementation of Genesis, Lion Parcel's internal Warehouse Management System (WMS), in enhancing operational efficiency at the Gunung Krakatau Branch in Medan. The research method used is descriptive qualitative with a case study approach. Data was obtained through direct observation, semi-structured interviews with warehouse and operations staff, as well as internal company documentation. The research findings indicate that the implementation of Genesis has had a positive impact on several efficiency indicators, including faster sorting processes, improved stock recording accuracy, reduced human error, real-time data access, and enhanced operational reporting quality. The system has also contributed to a significant decrease in customer complaints. However, the implementation of Genesis also faces several challenges, such as human resource adaptation to new technology, reliance on internet connectivity, and the need for updated standard operating procedures (SOPs). Overall, the Genesis system holds great potential to be further developed as part of Lion Parcel's digital transformation in logistics management. Its implementation not only improves operational efficiency at the branch level but can also serve as a strategic digitalization model to be widely applied throughout the company’s distribution network.